(untitled) (Journal of Health Sciences, 2020)
Introduction: Insufficient physical activity is one of the leading public health problems in the world, but also in Bosnia and Herzegovina. Modern civilization is characterized by a significant decrease in physical activity, and the number of people whose lifestyle can be called sedentary has never been higher, which is especially emphasised among children and adolescents. Aim of the study is to examine public health significance of physical activity on the occurrence and the degree of obesity in children and adolescents in primary and secondary schools and to determine the applicability of the Fels questionnaire on physical activity of children in rural areas of Bosnia and Herzegovina. Methods: We used a transversal research method of a cross-sectional study at a one-time point, and for obtaining results we used the Fels physical activity questionnaire for children and measurement protocol. Results: 276 primary and secondary school students in two cities participated in this survey. Respondents in Busovača are more physically active than their peers in Sarajevo. One-third of the total number of respondents is overweight and obese, and respondents in Sarajevo are significantly more nourished than their peers in Busovača. The Fels questionnaire is conditionally applicable, especially in rural areas. Conclusion: This study confirmed that the Fels questionnaire for assessing the level of physical activity for children and young people, which is the general instrument for research of physical activity in children, is too generalized because it is based on a homogeneous urban population.